Strategizing under institutional duality: A quantitative analysis of multinational responses to geopolitical decoupling - Zhang, Boyang (Edelweiss Applied Science and Technology, 2025)
A new era of institutional duality in international business has been introduced through the rise of geopolitical decoupling, particularly between the United States and China. In such competing logics of globalization and de-globalization, multinational enterprises (MNEs) have to balance cost-efficiency with security and value-based imperatives. While this shift has been identified through recent conceptual research, there is limited empirical illustration of the change in strategy intensity, orientation, and timing. This study constructs a three-dimensional framework to evaluate MNE responses to geopolitical decoupling along the axes of substantiveness, alignment shift, and temporal adaptiveness, assessing how MNEs adjust their operations, strategic orientations, and timing mechanisms under institutional pressure. Based on this analysis, we adopt clustering techniques to derive distinct empirical strategy profiles and test how exposure to institutional pressures—measured by specificity and destructiveness—influences response behavior. The results reveal a spectrum of adaptive strategies beyond traditional typologies, including preemptive repositioning, parallel engagement, and reactive substitution. This study contributes to international business and institutional theory by offering a scalable, multidimensional framework to analyze firm-level responses under unsettled institutional hierarchies and rising global bifurcation.